Decisive Factors of Eco-innovation in the Brazilian Electronic Complex* - Ansanelli, Stela Luiza De Mattos [UNESP]; Guratti, Israel De Moraes; Cintrão, Matheus Gonçalves; Sartoris, Alexandre [UNESP] (Universidade Estadual de Campinas, Instituto de Geociências, Departamento de Política Científica e Tecnológica, 2021)
Eco-innovation is an important concept, seeing as a strategy of transition to Green Economy, Circular Economy and Industrial Ecosystems. Internationally, many studies are being carried out searching for their determinants, but in low-income countries they are rare. The objective of this article is to investigate the determinants factors of Eco-innovations in the companies of the Brazilian electronic complex members of the Brazilian Association of the Electrical and Electronics Industry (ABINEE), through field research and descriptive statistical analysis and estimation of the binomial and multinomial Logit models. A sample of 48 companies was obtained which resulted from the models related to 1%. The results pointed out that the market, and not environmental regulation, has been the main determining factor of Eco-innovations since other variables need to be incorporated into the model (effective implementation of the regulation, institutional training and rigor/enforcement and type of environmental impact). Product Eco-innovation depends on the market, while those of process depend on regulations; more innovative firms are also eco-innovators and the size of the company matters, but not the source of the capital, as the practice of the branch is often not linked to the head office.
Keywords: Eco-innovation; Electronic complex; Determinants